Associate teachers' learning networks: a figurational analysis of initial teacher education. Issue 2 (29th April 2020) - Jones, Luke; Tones, Steven; Foulkes, Gethin
Abstract : Purpose: The aim of this paper is to use the lens of figurational sociology to analyse the learning networks of physical education (PE) associate teachers (ATs) in England. More specifically, it aims to develop a more adequate understanding of who is involved in the learning networks and how they influence ATs during their one-year postgraduate initial teacher education (ITE) programme. Design/methodology/approach: A total of 35 ATs within a university ITE partnership took part in the study during the final phase of their postgraduate programme. Questionnaires and semi-structured interviews were used to examine the nature and impact of the interdependent relationships that they had developed with other individuals and groups. A process of content analysis was used to identify and analyse patterns in the data. Findings: Mentors have the most influence over ATs. They support the inclusion of the ATs within the PE department, but elements of the mentors' role are contradictory and can unintentionally hinder the ATs' teaching. Mentors, teachers and tutors also share a common social habitus that ensures a degree of conformity within the PE community. New experiences tend to reinforce ATs' existing beliefs about the nature and practice of teaching PE. Practical implications: These findings have implications for providers of ITE in deciding who is involved in mentor training and how it is approached. If ATs are to be introduced to more innovative teaching approaches that promote change, then tutors need to collaborate with mentors and teachers to develop awareness of their often-unplanned influence. Originality/value: Applying the distinctive, and more generally sociological, concepts that make up the figurational perspective helped to develop a more adequate understanding of the ATs' learning networks. It provided an insight into the changing relationships that ATs have with their mentors and other individuals who work within the school and university context.